The effects of temperature and mobile phase on the retention of aliphatic carboxylic acids in hydrophilic interaction chromatography on zwitterionic stationary phases - Bohacova, Iveta; Halko, Radoslav; Jandera, Pavel (Wiley-VCH, 2016)
The influence of the mobile phase and temperature, on the retention behavior of seven aliphatic acids (pyruvic, gluconic, 2-oxoglutaric, tartaric, malic, oxalic, and citric acid) in hydrophilic interaction liquid chromatography on zwitterionic stationary phases with sulfobetaine and phosphorylcholine ligands is investigated. In agreement with the van't Hoff model, most acids show linear ln k versus 1/T plots. However, the retention of structurally symmetrical oxalic and tartaric dicarboxylic acids is almost independent of temperature, or slightly increases at rising temperature. The experimental parameters of the van't Hoff plots suggest positive entropic contributions to the retention of these symmetrical acids, possibly connected with changes inmolecular symmetry on their adsorption. The type of the zwitterionic stationary phase and the mobile phase composition (the molar concentration of acetate buffer and the volume fraction of acetonitrile) affect the retention and the selectivity of the separation of the acids.
Vliv teploty a mobilní fáze na retenci alifatických karboxylových kyselin v HILIC na zwitteriontových stacionárních fázích
Keywords: aliphatic carboxylic acids; hydrophilic interaction chromatography; retention mechanisms; temperature effects; thermodynamics; alifatické karboxylové kyseliny; chromatografie hydrofilních interakcí; retenční mechanismus; vliv teploty; termodynamika